Comparison of Parameters Physical and Chemical Surimi from Three Species of Fish Cultivation and Washing Frequency - ., Dasir; ., Suyatno; Zuryani, Helmi (International Journal of Engineering and Technology, 2019)
The availability of marine fish as surimi raw material will experience obstacles because there is no effective cultivation effort. In other conditions currently the cultivation and production of catfish (Clariasbatracus), catfish (Pangasiuspangasius) and tilapia (Oreochromis-mossambicus) have been quite successful and increasing, but there has been no processing effort to become surimi. This study aims to determine the physical and chemical characteristics of surimi from cultured fish species. The results showed that the three fish species could produce surimi with good physical and chemical properties of surimi. Tilapia species with washing frequency 3 times produce the best surimi compared to catfish (Clariasbatracus), catfish (Pangasiuspangasius).Â Â